2012
DOI: 10.5365/wpsar.2012.3.3.002
|View full text |Cite
|
Sign up to set email alerts
|

Tracking oseltamivir-resistance in New Zealand influenza viruses during a medicine reclassification in 2007, a resistant-virus importation in 2008 and the 2009 pandemic

Abstract: No evidence was found to suggest that increased access to oseltamivir has promoted resistance. A probable importation event was documented for the global 2008 oseltamivir-resistant seasonal A(H1N1) virus nine months after it was first reported in Europe in January 2008.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A recent study conducted in New Zealand revealed all 2009 seasonal Influenza A (H1N1) viruses to be resistant to Oseltamivir with the IC 50 values between 305 nM to 7912 nM. Similar study conducted in Thailand reported IC 50 values between 165.76 nM to 840.77 nM [4,28]. The Oseltamivir-resistant isolate obtained from Mumbai also displayed extremely high IC 50 value of 1261 nM which was similar to 2009 seasonal Influenza A (H1N1) viruses circulating in New Zealand and Thailand.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A recent study conducted in New Zealand revealed all 2009 seasonal Influenza A (H1N1) viruses to be resistant to Oseltamivir with the IC 50 values between 305 nM to 7912 nM. Similar study conducted in Thailand reported IC 50 values between 165.76 nM to 840.77 nM [4,28]. The Oseltamivir-resistant isolate obtained from Mumbai also displayed extremely high IC 50 value of 1261 nM which was similar to 2009 seasonal Influenza A (H1N1) viruses circulating in New Zealand and Thailand.…”
Section: Discussionmentioning
confidence: 87%
“…Antiviral agents confer significant prophylactic and therapeutic benefits during seasonal Influenza outbreaks and unexpected Influenza pandemics [3]. The development and occurrence of antiviral drug resistance in human Influenza viruses has been extensively studied over the last decade [4]. Initial analysis of Influenza A (H1N1) pdm 09 revealed that the virus was resistant to the Adamantanes class of drugs that inhibit the M2 ion channel [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the virus can acquire resistance to NIs by developing single point mutations (Ferraris and Lina, 2008). The ability of the virus to develop resistance against NIs depends upon enzyme mutations, and therefore, it is important to monitor the sensitivity of new influ-enza strains to NI drugs (Hall et al, 2009;Hall et al, 2012). The existing methods for testing viral resistance to a particular antiviral drug are time-consuming, and results can vary with methods (Okomo-Adhiambo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%